Cow's milk protein intolerance in adolescents and young adults with chronic fatigue syndrome. (3rd June 2016) - Rowe, Peter C.; Marden, Colleen L.; Jasion, Samantha E.; Cranston, Erica M.; Flaherty, Marissa A. K.; Kelly, Kevin J.
Abstract: Aim: To examine the prevalence, clinical features and influence on illness severity of cow's milk protein intolerance in young people with chronic fatigue syndrome. Methods: In a two‐year prospective study of 55 adolescents and young adults with chronic fatigue syndrome, we defined intolerance to milk protein if subjects reported (i) no evidence of immediate or anaphylactic reactions to milk, (ii) at least 2 of the following 3 chronic symptoms: gastroesophageal reflux, early satiety and epigastric/abdominal pain, (iii) improvement in upper gastrointestinal symptoms on a milk protein elimination diet and (iv) at least 2 recurrences of upper gastrointestinal symptoms >two hours following open re‐exposure to milk protein. Subjects completed three quality of life surveys at baseline and at six months. Results: The mean (SD) age of the 55 participants was 16.5 (2.1) years. Seventeen (31%; 95% CI, 19–43%) met study criteria for cow's milk protein intolerance. Compared to milk‐tolerant subjects, milk‐sensitive participants had significantly worse health‐related quality of life at baseline but not at six months (after institution of the milk‐free diet). Conclusion: Cow's milk protein intolerance is a common problem in young people with chronic fatigue syndrome and is a treatable contributor to their symptoms.